2003
DOI: 10.1177/147323000303100513
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin in the Treatment of Acute Maxillary Sinusitis after First-Line Treatment Failure and Acute Sinusitis with High Risk of Complications

Abstract: This multicentre, prospective study evaluated the efficacy and safety of 7-day oral moxifloxacin (400 mg/day) for treatment of acute maxillary sinusitis after first-line treatment failure (group 1), and acute sinusitis with high risk of complications (group 2). Two hundred and fifty-eight patients with radiologically confirmed acute sinusitis were enrolled by 52 investigators; 216 patients (83.7%) qualified for per protocol efficacy analysis (group 1, n = 175; group 2, n = 41), and 92 for bacteriological analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…Many clinical studies have shown the efficacy of moxifloxacin in the treatment of acute maxillary sinusitis (Arrieta et al, 2007;Gehanno et al, 2003;Johnson et al, 2008;Rakkar et al, 2001;Zhou et al, 2010). In our opinion, the microbiological results of this study suggest that clinical trials should be designed to investigate the clinical usefulness of moxifloxacin in the treatment of chronic maxillary sinusitis also.…”
Section: Discussionmentioning
confidence: 92%
“…Many clinical studies have shown the efficacy of moxifloxacin in the treatment of acute maxillary sinusitis (Arrieta et al, 2007;Gehanno et al, 2003;Johnson et al, 2008;Rakkar et al, 2001;Zhou et al, 2010). In our opinion, the microbiological results of this study suggest that clinical trials should be designed to investigate the clinical usefulness of moxifloxacin in the treatment of chronic maxillary sinusitis also.…”
Section: Discussionmentioning
confidence: 92%
“…The combination of potent pharmacodynamic activity and high clinical and bacteriologic efficacy indicates that the newer fluoroquinolones are an attractive option for the treatment of ABRS. In a recent study by Gehanno et al (56), moxifloxacin was shown to have excellent clinical and bacteriologic efficacy in patients with ABRS for whom previous antibiotic therapies had failed (97.2% clinical success) or who had severe ABRS (95.2% clinical success). Moxifloxacin has been shown to have higher therapeutic efficacy than cefuroxime axetil and trovafloxacin in the treatment of ABRS (57,58).…”
Section: Antimicrobial Therapy For Abrsmentioning
confidence: 98%
“…Moxifloxacin ensures an excellent coverage of the microorganisms associated with ABS, usually S. pneumoniae, H. influenzae and M. catarrhalis, and provides a rapid bacteriological eradication in the first 4 days of therapy [40]. The clinical and bacteriological efficacy of moxifloxacin appears to be at least similar to other current antibiotics recommended in ABS, such as cefuroxime or amoxicillin-clavulanate [41,42], and is a valuable therapeutic option in case of treatment failure or sinusitis with risk factors for complication [43]. Finally, once-daily administration may significantly improve patient adherence.…”
Section: Acute Sinusitismentioning
confidence: 98%